2020
DOI: 10.5194/bg-17-901-2020
|View full text |Cite
|
Sign up to set email alerts
|

Microtopography is a fundamental organizing structure of vegetation and soil chemistry in black ash wetlands

Abstract: Abstract. All wetland ecosystems are controlled by water table and soil saturation dynamics, so any local-scale deviation in soil elevation and thus water table position represents variability in this primary control. Wetland microtopography is the structured variability in soil elevation and is typically categorized into a binary classification of local high points (hummocks) and local low points (hollows). Although the influence of microtopography on vegetation composition and biogeochemical processes in wet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 67 publications
(89 reference statements)
0
18
0
Order By: Relevance
“…This microtopographic control on plant density and diversity is evident across systems: in the U.S. southeastern coastal plain (Anderson et al, 2009;Duberstein & Conner, 2009), northeastern U.S. tidal freshwater swamps (Courtwright & Findlay, 2011;Hörnberg, Ohlson, & Zackrisson, 1997;Økland et al, 2008), tropical freshwater swamp forests (Koponen et al, 2004), and tropical ombrotrophic peat swamps (Lampela et al, 2014). The preference for hummocks is particularly true for woody midstory and overstory species, but hummocks also exhibit greater understory diversity of both vascular plants and mosses (Diamond et al, 2020; but see Peterson & Baldwin, 2004). While not as pronounced as differences in woody vegetation, in some systems like salt and freshwater marshes that lack woody vegetation, hummocks are also associated with greater abundances of herbaceous species than hollows (Fogel et al, 2004;Langlois, Bonis, & Bouzillé, 2003;Shen et al, 2006).…”
Section: Biotic Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…This microtopographic control on plant density and diversity is evident across systems: in the U.S. southeastern coastal plain (Anderson et al, 2009;Duberstein & Conner, 2009), northeastern U.S. tidal freshwater swamps (Courtwright & Findlay, 2011;Hörnberg, Ohlson, & Zackrisson, 1997;Økland et al, 2008), tropical freshwater swamp forests (Koponen et al, 2004), and tropical ombrotrophic peat swamps (Lampela et al, 2014). The preference for hummocks is particularly true for woody midstory and overstory species, but hummocks also exhibit greater understory diversity of both vascular plants and mosses (Diamond et al, 2020; but see Peterson & Baldwin, 2004). While not as pronounced as differences in woody vegetation, in some systems like salt and freshwater marshes that lack woody vegetation, hummocks are also associated with greater abundances of herbaceous species than hollows (Fogel et al, 2004;Langlois, Bonis, & Bouzillé, 2003;Shen et al, 2006).…”
Section: Biotic Compositionmentioning
confidence: 99%
“…Hence, it is critical to understand and maintain these patterns through effective management of the underlying processes that maintain microtopographic feedbacks. Fortunately, detailed topographic data sets like those currently emerging (Graham et al, 2020;Stovall, Diamond, Slesak, McLaughlin, & Shugart, 2019) are becoming more widely available to better assess where different patterns occur (Diamond et al, 2020) and to infer the underlying processes from which they arise (Acharya et al, 2017;Rietkerk, Dekker, De Ruiter, et al, ). We suggest that diagnosing microtopographic pattern to understand feedback processes can help inform model predictions, management decisions, and restoration efforts.…”
Section: Microtopographic Pattern Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential to study the micro-topography of wetland ecosystems since it influences soil spatial heterogeneity through the physical and chemical properties, which, in turn, significantly influence meadow plant growth and survival (Deák et al, 2015;Oddi et al, 2019;Rose & Malanson, 2012). The geometry and spatial distribution of the hummock-depressions complex influence material circulation and energy flows in marshes, in addition to soil nutrient and particle characteristics (Diamond et al, 2019;Pintaldi et al, 2016;Zhao et al, 2020). Furthermore, they mediate the feedback between community structure and ecosystem functionality and enhance spatial variability in soil resources.…”
Section: Introductionmentioning
confidence: 99%
“…For alpine wetlands, the scale is micro (e.g., <1 m 2 ) for some resources such as water, nutrients, and light (Diamond et al, 2019;Vivian-Smith, 1997), and the hummock-depression microtopography in the alpine marshy wetlands in Sanjiangyuan in western China is on a miniature scale of this type. Despite the existence of several theories to explain the formation of hummock-depression micro-topography (Diamond et al, 2019;Edgar, 1998;Li et al, 2018;Tallis & Livett, 1994;Wang et al, 1997), no researcher has compared the physical and chemical properties of hummocks and depressions in the alpine marshy wetlands quantitatively, even though some authors have reported interactions between the development of alpine marshy wetlands and moisture, climate change, and litter decomposition (Wang et al, 2007;Zhang et al, 2016;Zhao et al, 2020). Therefore, it remains unclear how hummock-depression complexes vary under different levels of degradation severity, and how such variations influence vegetation and soil interactions between hummocks and depressions along degradation gradients.…”
Section: Introductionmentioning
confidence: 99%